Major and trace element geochemistry of Permo-Triassic granitoids from NW Sonora, Mexico: Constraints on the origin of the Late Paleozoic-early Mesozoic Cordilleran magmatic arc along SW Laurentia - Iriondo, Alexander; Martines Torres, Luis; Arvizu, Harim; Perez-Arvizu, Ofelia; Lozano-Santa Cruz, Rufino; Velazquez-Santaliz, Andres; Paz-moreno, Francisco; Izaguirre, Aldo (2022)
Permo-Triassic granitoids (PTGs) (284–224 Ma) crop out in Sierra Los Tanques (SLT) and surrounding areas in NW Sonora, Mexico. Based on mineralogical and geochemical characteristics, the PTGs are subdivided into three main suites: melanocratic (MS), leucocratic (LS) and pegmatitic-aplitic (PAS) suites. MS has I-type signatures (mostly metaluminous: biotite and hornblende), while LS is weakly peraluminous with biotite, muscovite, and garnet. PAS is composed of garnet-bearing pegmatite-aplite dikes of Permo-Triassic age. MS is slightly older than LS based upon field relations and age dating. PAS cut both granitoid suites and local Paleoproterozoic banded gneisses. PTGs are petrologically and geochemically classified as granodiorites, granites, and quartz monzonites, with medium-to high-K calc-alkaline affinity, and volcanic-arc granite (VAG) signatures. The enrichment in LILE (such as K, Rb, Ba, Sr, and Pb) and LREE over HFSE and HREE, respectively, together with negative Nb, Ta, P, and Ti anomalies, suggest derivation from a crustal source in a continental arc setting. Trace-element ratios of Ba/Ta≫1000, Th/Yb > 1, and Th/Ta>6–20 also support a setting in an active continental margin. All these geochemical features imply that crustal assimilation did play a major role in magma genesis. Crustal contamination is supported by field evidence, including xenoliths, stoped blocks, and roof pendants of Proterozoic basement rocks (Yavapai-type? crust). We propose that the PTGs from NW Sonora formed in a continental arc setting likely derived from the heat-fluxed melting of crustal material induced by mafic (basaltic?) underplating, thus the PTGs record the initiation of subduction and the generation of the early magmas in the nascent Late Paleozoic Cordilleran arc in SW Laurentia.